1. ## trig sub

Find the following integral:

$\int e^x \sqrt{1-e^{2x}}$

2. Originally Posted by qzno
Find the following integral:

$\int e^x \sqrt{1-e^{2x}}\,dx$
Let $e^x=\sin\theta$

Thus, $e^x\,dx=\cos\theta\,d\theta$

The integral becomes $\int\cos\theta\sqrt{1-\sin^2\theta}\,d\theta=\int\cos^2\theta\,d\theta$

Now recall that $\cos^2\theta=\frac{1+\cos\!\left(2\theta\right)}{2 }$

Can you continue the problem?

3. dont you mean that:

$

$
$\int\sin\theta\sqrt{1-\sin^2\theta}\,d\theta
$

because

$
e^x = sin\theta$

4. ooh my bad, you did some cancelling there i see haha

5. I got the answer to be:

$
sin^{-1} (e^x) - \frac{e^x \sqrt{1-e^{2x}}}{2} + C$

Is this correct?

6. Originally Posted by qzno
I got the answer to be:

$
sin^{-1} (e^x) - \frac{e^x \sqrt{1-e^{2x}}}{2} + C$

Is this correct?
Close...

When you integrate $\tfrac{1}{2}\int 1+\cos\left(2\theta\right)\,d\theta$, you get $\tfrac{1}{2}\theta+\tfrac{1}{4}\sin\left(2\theta\r ight)+C=\tfrac{1}{2}\theta+\tfrac{1}{2}\sin\theta\ cos\theta+C$, where $\sin\left(2\theta\right)=2\sin\theta\cos\theta$

Now substituting back in, we have $\theta=\sin^{-1}\left(e^x\right)$, $\sin\theta=e^x$, and $\cos\theta=\sqrt{1-e^{2x}}$

Therefore, $\tfrac{1}{2}\theta+\tfrac{1}{2}\sin\theta\cos\thet a+C=\boxed{\tfrac{1}{2}\left(\sin^{-1}\left(e^x\right)+e^x\sqrt{1-e^{2x}}\right)+C}$

7. excellent thank you : )